2011
DOI: 10.1002/fld.2374
|View full text |Cite
|
Sign up to set email alerts
|

A study on the mechanism of high‐lift generation by an insect wing in unsteady motion at small Reynolds number

Abstract: SUMMARYThe aerodynamic force and flow structure of a wing performing an unsteady motion at small Reynolds number (Re = 4000) is calculated by solving Navier-Stokes equations. Calculations were conducted for steady motion, simple unsteady motions suc as azimuth rotation, pure translation, feathering, etc., which can provide a basis for understanding the more complicated hovering flight. At Re = 4000, the delayed stall mechanism was noted during the azimuth rotation of a wing due to span wise flow. In azimuth ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…From Table 1, the maximum lift is 8.59×10 −6 N. So the beetle does not meet the flight conditions. This findings conform to the findings of other studies on flying under steady flow condition at low Reynolds number range [27,37] . Wootton [12] suggested that the flying capabilities and various flight skills of insects are mostly due to that there are various wing types and complex wing movement patterns.…”
Section: Flight Simulation Of Beetle At Quasi-steady Statesupporting
confidence: 93%
“…From Table 1, the maximum lift is 8.59×10 −6 N. So the beetle does not meet the flight conditions. This findings conform to the findings of other studies on flying under steady flow condition at low Reynolds number range [27,37] . Wootton [12] suggested that the flying capabilities and various flight skills of insects are mostly due to that there are various wing types and complex wing movement patterns.…”
Section: Flight Simulation Of Beetle At Quasi-steady Statesupporting
confidence: 93%
“…Since stronger positive vorticity layers exist at the trailing edge of the cross sections at 31.26°↑ compared to 38.36°↑, this has caused the higher rate of lift coefficient at 31.26°↑ (Figure 9). 20
Figure 9.Contours of vorticity at Re = 10,000; (a) mean angle of attack = 24° and the angle 31.26°↑, (b) mean angle of attack = 30° and the angle 38.36°↑.
…”
Section: Resultsmentioning
confidence: 99%
“…The wing starts from rest in still air and achieves a constant angular velocity after moving through an azimuth angle of 20˚. It is worth mentioning that the duration of the acceleration phase is immaterial in the context of the delayed stall, as confirmed by Hamdani and Naqvi (2010).…”
Section: Wing Kinematicsmentioning
confidence: 74%